Polysaccharide hydrogel incorporated carbon nanofiber microelectrode for designing neural interfaces - Torris, Arun; Badiger, Manohar V. (Journal of Bionic Engineering, 2019)
Bionic devices are an integral part of human life, and continuous innovations in their design and functions with the help of nanotechnology has revolutionized the area of neuroscience and technology. Bio-interfaces play a key role in bionic devices such as neural implants for efficient transfer of the signal to smart prosthetics. We report here on the design of a new microelectrode, comprising Carbon Nanofiber (CNF) and a biopolymer, namely carboxymethyl xyloglucan (CMX) hydrogel inside the CNF, which enhances the current density across the interface. Microelectrode was prepared by in-situ cross-linking of CMX inside CNF, with optimized CMX: CNF ratio, resulting in continuous ionic channels confined within the hollow core of CNF. Electron microscopy images of microelectrodes illustrate the formation of CMX hydrogel network inside the CNF hollow core without wrapping its surface. The presence of hydrogel in the CNF was confirmed by Scanning Electron Microscope (SEM) and Transmission Electron Microscopy (TEM). The electrochemical studies indicate the enhancement in charge density as well as the active surface area of the microelectrodes due to the presence of CMX hydrogel network. These microelectrodes have great potential as neural interfaces for designing smart prosthetics with voluntary control.